Determinantes da propensão à poupança para a reforma em Portugal - Figueiredo, Teresa Carlota Guedes Machado Lemos de (2018)
Dissertation presented as the partial requirement for obtaining a Master's degree in Statistics and Information Management, specialization in Risk Analysis and Management